-1x-3=3

Simple and best practice solution for -1x-3=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1x-3=3 equation:



-1x-3=3
We move all terms to the left:
-1x-3-(3)=0
We add all the numbers together, and all the variables
-1x-6=0
We move all terms containing x to the left, all other terms to the right
-x=6
x=6/-1
x=-6

See similar equations:

| (x+10)*x=1200 | | X+3=2.5+x | | 8j+4j-6j-j=20 | | 5x+5x-3x=14 | | -75=13e | | 21x^2-27x-30=0 | | d-d+2d-d=20 | | 9x+8=6x+(-11) | | 5(x+9)+8(2x-3)=6(3x-8)+3(x-2) | | 8n+6n-13n=6 | | 16-x-5=5 | | 5b+b+4b-8b=20 | | n+1+1-5=-8(n-3)+2(1+4n) | | 11v-2v-8v=8 | | 4w-w-3w+2w=18 | | 8v=23 | | 10h-10h+6h=18 | | w/7-3.4=-20.9 | | 40+4b=64 | | -8+2x=2(x-6) | | 287=7x.x= | | 300x+1200=2700 | | C+c+2c-c=15 | | 204=-8(-4-5p+3p | | 11n-4n-6n=15 | | -5(4p+7)=125 | | 18c-16c=14 | | 20=x*x-6*0.5 | | J-j+j=7 | | (3y)/5=40 | | 20=x*x-6*05 | | 8w​ −12=−5 |

Equations solver categories